Estrategias metodológicas y su influencia en el desarrollo de habilidades cognitivas en los niños/as de segundo grado de la Escuela de Educación Básica Juan E. Verdezoto, cantón Babahoyo, Provincia Los Ríos, año 2020 - Campos Palma, Kerlly Carolina (2020)
The methodological strategies in the second-grade children of the “Juan E. Verdezoto” Basic Education school in the city of Babahoyo, Los Ríos province, are necessary to increase cognitive skills, allowing them to acquire important knowledge learning, also helps to reveal the deficiencies that teachers commit in the application of theoretical foundations. The objective of this case study was to examine the results of the development of cognitive skills in second-grade children of said institution, therefore, didactic methods were used, encompassing descriptive research with a type of exploratory design, since The influence that methodological strategies will have on the development of cognitive abilities in children was analyzed. The research was carried out with the collaboration of the children and the teacher of the indicated educational institution. A field investigation was carried out, through observation at the time when the pre-professional practices were carried out, so it could be evidenced that educators do not use the appropriate methodological strategies so that children do not have the correct participation and therefore this does not arouse interest in learning. The results obtained through the interviews and observation indicated that the teacher in charge of the second grade children must obtain didactic training in the knowledge of new methodological strategies that influence the development of cognitive skills in the children of the second grade second grade.